2019
DOI: 10.1016/j.bioactmat.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro corrosion of AZ31 magnesium alloys by using a polydopamine coating

Abstract: Magnesium alloys are candidates to be used as biodegradable biomaterials for producing medical device. Their use is restricted due to the high degradation rate in physiological media. To contribute to solving this problem, a polydopamine (PDOPA) layer could be used to increase adhesion between the metallic substrate and external organic coating. In this paper, the corrosion behaviour of samples was investigated to determine their performance during the long-term exposure in simulated body fluid. Electrochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…This behavior highlighted that the combination of PEO with epoxy resin provided good corrosion resistance in comparison to all the tested samples [51]. According to Carangelo [52], a higher corrosion potential was provided by the epoxy resin deposited on the sample. Summing up, the impedance spectra obtained during the EIS tests indicate progressive coating degradation in contact with an aqueous solution containing chloride ions.…”
Section: Eis Testmentioning
confidence: 76%
“…This behavior highlighted that the combination of PEO with epoxy resin provided good corrosion resistance in comparison to all the tested samples [51]. According to Carangelo [52], a higher corrosion potential was provided by the epoxy resin deposited on the sample. Summing up, the impedance spectra obtained during the EIS tests indicate progressive coating degradation in contact with an aqueous solution containing chloride ions.…”
Section: Eis Testmentioning
confidence: 76%
“…Results from our previous studies have confirmed that LDH coating can improve in vitro and in vivo corrosion resistance of Mg-based materials [ 27 , 30 ]. PDA is a compact layer of polymer that can effectively prevent the penetration of liquid molecules and block the electron transfer between Mg substrate and corrosive solution, thus improving the corrosion resistance of the material [ 21 , 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…PDA has a thickness of ∼100 nm and functional groups of catechol, amine, and imine. PDA has been deposited on biomedical Mg alloy for better corrosion resistance and biocompatibility [ 20 , 21 ]. PDA coating is also reported as a general strategy to enhance osteogenic differentiation of orthopedic implants [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mg-based alloys exhibit uncontrollable rapid corrosion when used as temporary implant materials, it is a serious problem on account of the chemical properties of Mg [ [16] , [17] , [18] ]. Moreover, such phenomenon signifies that Mg-based alloys will lose their expected inherent function.…”
Section: Introductionmentioning
confidence: 99%